The role of religion and spirituality in the Latina/o student university experience - Rodriguez-Chavez, Mirta (My University, 2024)
Despite the growing population of Latina/o students in the United States, those who are entering college are not graduating at the same rate as their white counterparts. The six-year Hispanic student graduation rate was 8% lower than that of white students (U.S. Census Bureau, 2020). The Latina/o educational attainment gap still exists and continues to be a major concern. The purpose of this narrative inquiry was to examine the role religion and spirituality play in the Latina/o college student experience. This research study was developed around the research question: “What role do religion and spirituality play in the Latina/o higher education experience?” Participants were undergraduate students of Latina/o descent in their junior and senior year at a land grant University. This study extends the current literature by examining the influence of religion and spirituality has on Latina/o college students’ experiences.
Keywords: Religion; Spirituality; Latina/o; University; Experience